Effects of porcine somatotropin and dietary phosphorus on growth and bone criteria in gilts - Weeden, T.L.; Fitzner, G.E.; Hansen, J.A.; Friesen, K.G.; Johnston, M.E.; Schricker, B.R.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred-eight gilts with an average initial wt of 129 lb were utilized to determine the effects of porcine somatotropin (pST) and dietary phosphorus on growth performance and bone mineralization and mechanical properties during the finishing phase (129 to 230 lb) and a 35 d post-finishing phase. Gilts were injected daily with placebo (control) or 4 mg pST and fed diets containing .4, .8, or 1.2% P during the finishing phase. Administration of pST improved F/G 18%, increased ADG 8%, and decreased daily feed intake 9%. There was a quadratic response to P, because gilts receiving the .8% P diet were more efficient than gilts fed either .4 or 1.2% P, regardless of whether they received pST or placebo. When pen wt reached 230 lb, half of the gilts were slaughtered and 1st rib, femur, and 3rd and 4th metacarpals were collected. First rib ash content increased linearly as the level of dietary P increased; however, pST administration had no effect on ash content. There was a pST x P interaction for rib bending moment, stress, and modulus of elasticity. Bone strength was maximized for control gilts at .8% P, whereas bone strength continued to increase as the level of dietary P was increased for pST-treated gilts. The remaining 54 gilts were individually fed 4 lb/d of a common diet for a 35 d post-finishing phase and then slaughtered. Gilts that received higher P levels in the finishing phase had higher rib ash content at the end of the post-finishing phase. There was a pST x P interaction for treatment combination received in the finishing phase on rib and femur bending moment post-finishing. Bone strength for pST-treated gilts receiving the .8 or 1.2% P diet in the finishing phased increased to levels exceeding those of control gilts by the end of the post-finishing phase, regardless of dietary P level control gilts were fed in the finishing phase. These data indicate that gilts administered pST in the finishing phase do not have higher Ca and P requirements than non-pST treated gilts to maximize growth performance. However, pST-treated gilts do have higher requirements for Ca and P than non-pST treated gilts to attain comparable bone strength in the finishing phase. Gilts receiving pST in the finishing phase demonstrate compensatory mineralization in the post-finishing phase, because bone strength increases to equal or exceed that of control gilts fed similar P levels.
Keywords: Swine; Repartition; Performance; Gilts; Phosphorus; Bone